2022
DOI: 10.1029/2022jb024234
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Magnetic Signals of Individual Magnetite Grains to Their Internal Magnetic Configurations Using Micromagnetic Models

Abstract: Paleomagnetic studies commonly try to extract from geological samples the primary characteristic remanent magnetization, acquired during rock formation (Butler, 1991). These studies put considerable effort in selecting rocks with a narrow magnetic grain size distribution. These are considered to have optimal recording properties, and are preferred because even careful stepwise demagnetization of bulk magnetic measurements cannot always reliably separate primary from secondary, or stable from unstable remanence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Cortés‐Ortuño et al. (2022) showed that PSD state particles present more accurate inversion results when considering the non‐dipolar components for small sample‐sensor distances (<1 μm). For larger sensor distances, the dipole as approximations are remarkably accurate, as the higher‐order moments decay rapidly with distance and therefore have less influence on the particle's magnetic signal.…”
Section: Discussionmentioning
confidence: 99%
“…Cortés‐Ortuño et al. (2022) showed that PSD state particles present more accurate inversion results when considering the non‐dipolar components for small sample‐sensor distances (<1 μm). For larger sensor distances, the dipole as approximations are remarkably accurate, as the higher‐order moments decay rapidly with distance and therefore have less influence on the particle's magnetic signal.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the application of the proposed algorithm to natural samples should fail for those PSD particles. Cortés-Ortuño et al (2022) give important insights about the matter, they showed that PSD state particles present more accurate inversion results when considering the non-dipole components for small sample-sensor distances (<1 𝜇m), but for larger sensor distances the dipole as approximations are remarkably accurate, as the higher-order moments decay rapidly with distance and therefore have less influence on the particle's magnetic signal. Thus, our approach can be considered reasonable to work with both particle SD and PSD states signals.…”
Section: Reliability Of Dipole Moment Approximationmentioning
confidence: 99%
“…In order to apply magnetic microscopy to paleomagnetic studies, it is necessary to recover from the magnetic images a large number of individual magnetic moments, corresponding to at least tens of thousands of stable fine-grained grains (< 1 µm), in order to provide statistical significance to the remanence vector (e.g., Berndt et al, 2016). Nowadays, with the development of magnetic microscopy techniques, this task is no longer limited by the resolution of magnetic microscopes (de Groot et al, 2018;Fu et al, 2020;Glenn et al, 2017;Lima et al, 2014;Weiss et al, 2007), but essentially by the intrinsic problem presented by the ambiguity in the inversion of potential field data (Barbosa and Silva, 2011;de Groot et al, 2021;Oliveira Jr. et al, 2015), and ultimately by the lack of a fast and automated way to recover such a large number of individual magnetic moments from a set of magnetic images (Cortés-Ortuño et al, 2022;Lima and Weiss, 2009;Lima et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these individual point sources very rarely correspond to the actual magnetization distribution within a magnetic material producing the measured magnetic field, they possess useful mathematical properties and can sometimes be related to physical quantities of interest [see, for instance, Cortes‐Ortuno et al. (2021, 2022) for an application of low‐order multipoles to constrain the internal magnetization structure of magnetic grains analyzed with micromagnetic tomography]. Two drawbacks of multipole expansions are that (a) multipoles with orders higher than that of a dipole are strongly dependent on the location of the origin, making their physical interpretation challenging (Lowes, 1994), and (b) multipoles are inefficient for representing extended sources, especially those with asymmetrical dimensions, because a very large number of terms is required to adequately reproduce the magnetic field of such source configurations.…”
Section: Introductionmentioning
confidence: 99%